Diagnóstico de las condiciones de seguridad y salud ocupacional para los empleados de la Avícola Mía de la ciudad de Calceta - Lucas Loor, Erick Joao (2019)
The objective of the present investigation was to carry out a diagnosis focused on occupational health and safety conditions in the employees of the Avícola Mía of the Mocochal site in Calceta city. The methodology used was the deductive, descriptive that helped to have clear ideas of where the problems originate and to know the current situation and the triple criteria where, at each risk found in the different work areas, the probability that produce an accident and the severity of the damage, which is favorable for workers because it gives them greater security and to improve the job performance in the company. With respect to the dangers within the poultry, it was found that there are very significant physical risk factors, which in turn are the most dangerous for the health of workers. These inconveniences arise due to the lack of training and at the same time due to the unconsciousness of the employees themselves when using their respective personal protective equipment. In Bolívar canton, the Poultry Mine maintains its productive chain, the breeding farm and the production of its own food, however, one of the main problems found in this organization is that the workers do not have the necessary work safety equipment, such such as: helmets, gloves, masks, clothing, etc., the same that are necessary to carry out their activities safely and avoid any type of accident at work